2020
DOI: 10.5603/cj.a2019.0005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative high-sensitivity troponin T as a predictor of sudden cardiac arrest in patients undergoing cardiac surgery

Abstract: Background: The usefulness of high-sensitivity troponin T (hs-TnT) as a predictor of sudden cardiac arrest (SCA) in patients undergoing valve surgery is currently unknown. Methods: A prospective study was conducted on a group of 815 consecutive patients with significant valvular heart disease that underwent elective valve surgery. The primary end-point was postoperative SCA. Results: The postoperative SCA occurred in 26 patients. At multivariate analysis of hs-TnT measured immediately after surgery (hs-TnT I) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…5 In the patients undergoing valve surgery, measuring postoperative high-sensitivity troponin T is recommended because its elevation is associated with a high risk of postoperative, sudden cardiac arrest. 16 The most likely cause of cardiac arrest in this patient was migration of an embolism from the site of previous surgery. This diagnosis was made based on clinical judgement, as well as the finding of the small emboli on the doppler ultrasound.…”
Section: Discussionmentioning
confidence: 82%
“…5 In the patients undergoing valve surgery, measuring postoperative high-sensitivity troponin T is recommended because its elevation is associated with a high risk of postoperative, sudden cardiac arrest. 16 The most likely cause of cardiac arrest in this patient was migration of an embolism from the site of previous surgery. This diagnosis was made based on clinical judgement, as well as the finding of the small emboli on the doppler ultrasound.…”
Section: Discussionmentioning
confidence: 82%
“…5 In the patients undergoing valve surgery, measuring postoperative high-sensitivity troponin T is recommended because its elevation is associated with a high risk of postoperative, sudden cardiac arrest. 16 The most likely cause of cardiac arrest in this patient was migration of an embolism from the site of previous surgery. This diagnosis was made based on clinical judgement, as well as the finding of the small emboli on the doppler ultrasound.…”
Section: Discussionmentioning
confidence: 82%
“…Duchnowski and colleagues reported that the hs TnT is a reliable predictor of cardiogenic shock necessitating mechanical circulatory support. Moreover, elevated troponin levels were associated with an increased risk of sudden cardiac arrest [ 26 , 27 ]. In contrast to our findings, Mehrpour et al [ 28 ] found no evidence of an increase in cTnI serum levels in patients with a healthy cardiovascular system following generalized CSE episodes.…”
Section: Discussionmentioning
confidence: 99%